The Influence of Reward and Punishment-based Conflict Resolution on The Performance and Loyalty of Elementary School Teachers - Haya, Haya; Wapa, Andi (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2024)
This research was conducted because of the problems of teacher loyalty and performance in elementary schools. This research aims to describe the effect of implementing reward punishment-based Conflict Resolution on the performance and loyalty of elementary school teachers. The research design uses a posttest only control group design. The research population of elementary school teachers was 401 participants. The sample consisted of 120 students who were divided into two experimental classes and two control classes using group random sampling techniques. Data analysis was carried out using ANOVA. The research results show the results of teacher performance and loyalty between those who follow reward and punishment-based conflict resolution policies and those who follow conventional policies with an F_cal value of 22.284 > Ftab (3.93). It can be concluded that there are differences in results between the group of teachers who took part in reward and punishment-based conflict resolution treatment and the teachers who took part in the conventional-based conflict resolution group.